Menilik Implementasi Perma No. 1 Th. 2014 (Studi Kasus Kerjasama Antara Stain Kediri Dengan P.A. Kab. Kediri Dalam Program Posbakum 2015) - Abdullah Taufik (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
The provision of legal services in the form of a court Posbakum program for PA Kediri is a new program that has never existed before, although it has been mandated by the Act. No. 50 in 2009 on the Religious Courts. For STAIN Kediri, an institutional cooperation program with the PA Kediri is a new program that has never been done before. Therefore, it is important to conduct a research on the cooperation between the LKBH STAIN Kediri and PA Kediri in Posbakum program 2015. This article attempts to explain the implementation of Perma No. 1 in 2014 based on PA Kediri, particularly in Posbakum program, the background of Memorandum of Understanding (MOU) between the LKBH STAIN Kediri and PA Kediri, and the constraints faced in the institutional cooperation. By using descriptive qualitative approach, the study concluded that the implementation of Posbakum in cooperation between the PA Kediri Â andÂ LKBH STAIN run in accordance with the rules of per-law's and adapted to local peculiarities. Although there are several obstacles, such as lack of accuracy of data collection by the officers of Posbakum, clarity of administration fees, labor discipline and coordination patterns that have not been effective.